Ecotourism Management Strategy for the Sei Gohong Tourism Village through Collaboration between the Community and the Government in Palangka Raya - Alpiani; Fitriana Selvia; Imanuel Jaya; Ditta Islammiyatul Khotimah (Green Publisher Indonesia, 2026)
Sei Gohong Tourism Village in Palangka Raya possesses significant ecotourism potential combining peat ecosystem uniqueness, orangutan conservation, and Dayak Ngaju cultural heritage. However, post-pandemic recovery has been hindered by damaged facilities, weak human resources, and suboptimal stakeholder synergy. This research aims to analyze internal and external factors and formulate a collaborative ecotourism management strategy. The method used was qualitative descriptive with IFE, EFE, and SWOT matrix analysis . The results of the analysis showed an internal score of 2.70 and an external score of 2.95 , which means that the natural and cultural potential is very strong and the market opportunities are very supportive, but hampered by weak infrastructure, human resources, and management. Synergy between stakeholders has also not run optimally. Sei Gohong Tourism Village in Palangka Raya possesses significant ecotourism potential combining peat ecosystem uniqueness, orangutan conservation, and Dayak Ngaju cultural heritage. However, post-pandemic recovery has been hindered by damaged facilities, weak human resources, and suboptimal stakeholder synergy.